UTILIZATION OF ART, CULTURE, AND TECHNOLOGY IN THE DEVELOPMENT OF TOURIST VILLAGES THROUGH POKDARWIS - Inderawati, Rita; Saputra, Ardi; Septiani, Yin Yin; Sepdwiko, Deria (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Purwosari Village gained recognition with the Embung Puri Idaman tourist attraction, the only tourist village in East Ogan Komering Ulu Regency. Managed by the Pokdarwis (Tourism Awareness Group), formed in 2022, the site is now facing challenges, including a decrease in the number of visitors. The causes include limited tourism creativity and innovation, economic capital, suboptimal marketing, and low community cohesion. To overcome this, online cultural arts and marketing training programs were held to boost Pokdarwis creativity, attract more visitors, and provide educational value for tourists. This training used the Asset Based Community Development (ABCD) approach and involved 40 participants, including Pokdarwis members, village officials, children, and village residents. The material provided includes training on the mini saron musical instrument, the bancakan weton procession, tourism management, and social media marketing. The results showed an increase in participants' knowledge from 11.5% to 75.5%, as well as an increase in creativity from those who only relied on nature and facilities as tourist attractions, now being able to play mini saron and understand the bancakan weton cultural procession. Interviews revealed that participants gained new motivation to promote local arts and culture, aiming to increase recognition and provide economic value for the village community.